PENYULUHAN BAHAYA SISTISERKOSIS DAN CARA PENYIMPANAN TELUR DI DESA TANAH PUTIH, KABUPATEN KUPANG, NTT - Dionesia Mogi; Felsi Atri Jedaut; Ferdinando Rua; Nelsi Rohi; Tekla Lanasakti; Theresia Tinenti; Tri Oematan; Yustina Petronela; Viktoriano Mbula; Novalino H. G. Kallau; Diana Agustiani Wuri; Annytha I. R. Detha; Larry R. W. Toha (Universitas Nusa Cendana, 2021)
Tanah Putih Village is a village in Kupang regency, NTT with the majority of people are working as breeders and farmers. That is why there are lots of pigs, chickens, and cows raised by the community. The purpose of the counseling is to educate farmers and breeders about the risk of cysticercosis for human beings and to give information on how to store eggs in a better way. The counseling carried out was done smoothly and the participants were enthusiastic to follow the activity which is shown by the questions and sharing they are given to the counselor during the community service activity. Thus, the people of Tanah Putih Village are expected to be able to understand and apply the topics that are given into their daily life.